2019
DOI: 10.1016/j.jcrimjus.2018.08.001
|View full text |Cite
|
Sign up to set email alerts
|

The influence of ‘High’ vs. ‘Low’ rape myth acceptance on police officers' judgements of victim and perpetrator responsibility, and rape authenticity

Abstract: Full bibliographic details must be given when referring to, or quoting from full items including the author's name, the title of the work, publication details where relevant (place, publisher, date), pagination, and for theses or dissertations the awarding institution, the degree type awarded, and the date of the award.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 42 publications
0
35
0
3
Order By: Relevance
“…Rape myths include beliefs about the victim's character, appearance, and behavior; the motivations and behavior of the offender; and the situational factors surrounding the offense (e.g., the area, time of day, method; Burt, 1980;Sleath & Bull, 2012) and can be broadly categorized into four categories: blaming the victim; exonerating the perpetrator; the belief that rape is not very common or serious; and the belief that only certain types of women are raped (Gerger et al, 2007;Lonsway & Fitzgerald, 1994). Rape myths have been found to be persistent across community and professional samples, and men consistently exhibit higher levels of RMA than do women (Gerger et al, 2007;Hine & Murphy, 2019;Persson et al, 2018;Suarez & Gadalla, 2010). Crucially, a large evidence base has found that RMA correlates with victim blame in rape cases by positioning women as the cause of rape (for a review, see Grubb & Turner, 2012), and it seems to play a particularly important role in assigning blame in acquaintance rape cases (Gravelin et al, 2018).…”
Section: Rmamentioning
confidence: 99%
“…Rape myths include beliefs about the victim's character, appearance, and behavior; the motivations and behavior of the offender; and the situational factors surrounding the offense (e.g., the area, time of day, method; Burt, 1980;Sleath & Bull, 2012) and can be broadly categorized into four categories: blaming the victim; exonerating the perpetrator; the belief that rape is not very common or serious; and the belief that only certain types of women are raped (Gerger et al, 2007;Lonsway & Fitzgerald, 1994). Rape myths have been found to be persistent across community and professional samples, and men consistently exhibit higher levels of RMA than do women (Gerger et al, 2007;Hine & Murphy, 2019;Persson et al, 2018;Suarez & Gadalla, 2010). Crucially, a large evidence base has found that RMA correlates with victim blame in rape cases by positioning women as the cause of rape (for a review, see Grubb & Turner, 2012), and it seems to play a particularly important role in assigning blame in acquaintance rape cases (Gravelin et al, 2018).…”
Section: Rmamentioning
confidence: 99%
“…Police officers are the "gatekeepers" of the criminal justice system and are usually the first to come into contact with crime victims. As such, they exert major influence on both the victim and the case (Hine and Murphy, 2019). Police work is discretionary by nature, and officer perception of cases, victims, and offenders may impact decisions, such as which cases are worth pursuing, amount of investigative efforts a case will receive, and how to conduct the investigation.…”
Section: Introductionmentioning
confidence: 99%
“…More recent research has also found relationships between police officers’ stereotypical beliefs about rape and judgments of victim credibility and rape authenticity (Hine & Murphy, 2019; O’Neal, 2019). For example, a large U.K. study ( N = 808) showed that police officers with high levels of rape myth acceptance attributed higher victim responsibility, lower perpetrator responsibility, and gave lower rape authenticity ratings compared to police officers with low levels of rape myth acceptance (Hine & Murphy, 2019).…”
Section: Police Attitudes and Case Decision-makingmentioning
confidence: 98%
“…More recent research has also found relationships between police officers’ stereotypical beliefs about rape and judgments of victim credibility and rape authenticity (Hine & Murphy, 2019; O’Neal, 2019). For example, a large U.K. study ( N = 808) showed that police officers with high levels of rape myth acceptance attributed higher victim responsibility, lower perpetrator responsibility, and gave lower rape authenticity ratings compared to police officers with low levels of rape myth acceptance (Hine & Murphy, 2019). Those with high levels of rape myth acceptance also gave particularly negative judgments to vignette scenarios that included rape myth-related information, leading the authors to conclude that there was a direct relationship between the attitudes of U.K. police officers and judgments of authenticity in hypothetical rape cases, which may in turn influence investigative and case processing decisions.…”
Section: Police Attitudes and Case Decision-makingmentioning
confidence: 98%